Radiologic findings in women after Autologous Fat Transfer (AFT) based breast reconstruction: A Systematic Review - M.E.P. Rijkx; E. Bernardi; S.J. Schop; E.M. Heuts; M.B.I. Lobbes; J.E. Hommes; A. Piatkowski de Grzymala; T.J.A. van Nijnatten (JPRAS Open)
Purpose: Autologous fat transfer (AFT) is increasingly used in breast reconstructive surgery. Due to post-surgical changes, in breast imaging after AFT, it can be challenging to differentiate between benign and suspicious findings. This systematic review aimed to present an overview of the literature on breast imaging after AFT-based breast reconstruction. The descriptive radiologic findings focus on different breast imaging modalities (i.e., mammography (MG), ultrasound (US), and breast magnetic resonance imaging (MRI)) to provide an overview of the most commonly reported benign and suspicious findings. Results: The literature search yielded 20 studies from 2006-2022 that reported AFT-based breast reconstructions and included the radiologic evaluation of the included breast imaging modalities. Only six of the 20 included studies provided qualitative descriptions of radiologic findings. Fat necrosis was most frequently reported. On MG, fat necrosis was described in a variety of stages such as oil cyst or cytosteatonecrosis with or without calcifications. On US, it was described as a nonvascular hypo- or anechoic mass, and on breast MRI, it was most frequently reported as hypointense homogenous architectural distortion. Additional biopsies to differentiate between benign and malignant findings after AFT-based breast reconstruction were reported in 13 of the 20 studies. Among all included studies in the current review, a total of 34 of 137 biopsies were considered malignant (24.8%). Conclusion: Qualitative descriptions of the reported radiologic findings after AFT for breast reconstruction were limited. Additional biopsies can be considered to differentiate between benign and suspicious findings. More experience and research are necessary to improve the interpretation of breast imaging after AFT-based breast reconstructions.